Code of federal regulations. 9, Animals and animal products. - United States. Department of Agriculture; United States. Office of the Federal Register (Washington, D.C. : Office of the Federal Register, National Archives and Records Service, General Services Administration : United States Government Printing Office)
Special edition of the Federal register, containing a codification of documents of general applicability and future effect as of ... with ancillaries.
Volumes for <1989-> distributed to some depository libraries in microfiche.
Volumes for <1981-> issued in parts.
Mode of access: Internet.
Volumes for 1986- published by the Office of the Federal Register, National Archives and Records Administration.
2012, pts. 1 to 199.
1981, pts. 1 to 199; title from cover.
Keywords: Meat industry and trade -- Law and legislation; Animal industry -- Law and legislation; Meat -- legislation & jurisprudence; Food Inspection -- legislation & jurisprudence; Animals, Domestic -- legislation & jurisprudence; Meat industry and trade -- Law and legislation -- United States -- Periodicals; Animal industry -- Law and legislation -- United States -- Periodicals; United States; United States; Periodicals; Web sites; Periodicals; Government publications